Pengalaman Ibu Merawat Anak Usia Prasekolah (3-6tahun) Dengan Perilaku Ketergantungan Gadget Di Masa Pandemi Covid 19 Di Kabupaten Cianjur - Eva Martini; Sally Yustinawati Suryatna (Universitas Malahayati Lampung, 2022)
ABSTRACT The Covid 19 outbreak in 2020 began to enter the State of Indonesia. The emergence of the Covid-19 outbreak has caused various problems. The Covid 19 virus does not only attack humans directly but has an impact on the world and affects social life in various countries. The Covid pandemic has also had an impact on the world of education. The previous learning was done face-to-face (offline), but during the Covid-19 pandemic, learning used an online system (online). One of the devices used during online learning is a gadget. School-age children are included in the age of Golden Age Period. Gadgets have a negative impact on children's development. How to overcome so that children do not experience gadget dependence, there need to be managed the use of gadgets. Mother has the role of providing the needs of honing, loving, and nurturing. This study aims to explore the experience of mothers caring for preschool-aged children (3-6 years) with gadget dependence behavior during the Covid-19 pandemic. The research design used a qualitative descriptive phenomenological approach. The results of the study contained four themes, namely the reason why mothers give gadgets to children, the impact of gadgets on preschoolers, descriptions of gadget dependence on preschoolers, mother's expectations about the use of gadgets in online learning. The need for assistance for preschool children when playing with gadgets in order to minimize the negative impact of gadgets on the development of preschool children. Keywords: Preschoolers, Gadget Addiction, Covid-19 Pandemic ABSTRAK Wabah Covid 19 tahun 2020 mulai masuk ke Negara Indonesia. Munculnya wabah Covid 19 menimbulkan berbagai masalah. Virus Covid 19 tidak hanya menyerang manusia secara langsung tetapi memberikan dampak terhadap dunia serta mempengaruhi kehidupan sosial di berbagai negara. Pandemi Covid berdampak juga terhadap dunia pendidikan. Pembelajaran yang sebelumnya dilakukan secara tatap muka (luring), tetapi pada masa pandemic Covid 19 pembelajaran menggunakan sistem online (daring). Perangkat yang digunakan saat pembelajaran daring salah satunya adalah gadget. Anak usia sekolah termasuk kedalam usia The Golden Age Periode. Gadget memiliki dampak negatif terhadap perkembangan anak. Cara mengatasi agar anak tidak mengalami ketergantungan gadget perlu adanya manajemen dalam penggunaan gadget. Ibu mempunyai peran memberikan kebutuhan asah, asih, asuh. Penelitian ini bertujuan untuk mengeksplorasi mengenai pengalaman ibu merawat anak usia prasekolah (3-6tahun) dengan perilaku ketergantungan gadget di masa pandemi Covid 19. Desain penelitian menggunakan metode kualitatif pendekatan fenomenologi deskriptif. Hasil penelitian terdapat empat tema yaitu alasan ibu memberikan gadget terhadap anak, dampak gadget untuk anak prasekolah, gambaran ketergantungan gadget pada anak prasekolah, harapan Ibu tentang penggunaan gadget dalam pembelajaran daring. Kesimpulan perlu adanya pendampingan terhadap anak prasekolah ketika bermain gadget agar meminimalisisr dampak negative gadget terhadap perkembangan anak prasekolah. Kata Kunci: Anak Prasekolah, Ketergantungan Gadget, Pandemic Covid 19